Process as Labour: Struggles for Anti-Oppressive/Anti-Racist Change in a Feminist Organization - Moffatt, Ken; Barnoff, Lisa; George, Purnima; Coleman, Bree (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2009)
Even though anti-oppression social work practice (AOP) and social change has been central to the literature of social work surprisingly little has been witten about how worlcers struggle daily to integrate anti-oppressive agendas. In this paper we illustrate how in a progressive feminist organization individuals committed to social justice continue to struggle as they work towards anti-oppressive change. Through the results of a case study with a feminist organization that bases its vision on an anti-oppressive and anti-racist model of practice, we make the case for a focus on process as a critical component of the labour of anti-oppression work. Through this lens, we are able to outline some of the ongoing struggles that occur within progressive organizations as organizational members work toward anti-oppressive change. Part of the job of progressive social service workers is to reflect upon the process of working together within an organization as well as the purpose and nature of their work. Our research finds that the processml nature of antioppression work is ongoing, open ended and irresolvable. That is, struggle is to be expected when agencies are working to implement anti-oppressive pactices. Mgme si lu pratique anti-oppressive du travail social et le pogr2s social sont au CEUT &S e’crits en service social, curieusement, on trouve tr2s peu de textes sur lu nature des combats quotidiens de l’anti-oppression. Duns cet article, les auteurs illuscrent comment, dans un organisme progressiste fe’rniniste, la re’sistance au changement anti-oppressif persiste. Parmi les actiuite’s du travailkur social progressiste, on trouve la re’flexion sur le processusdu travail de collaboration azi sein cl’un organisme ainsi que le but et la nature des t&hes h accomplir. La nature pocessuelle du travail anti-oppressif selnble &re inde’termine’e et impossible h re’souclre. Sur la base des re’sultats tire’s d’une e’tude de cas sur zm organisme fe’ministe qui fonde sa vision sur un mod& de pratiques anti-oppressives, les auteurs prgconisent de cibler le processus en tant que comnposante critique des activite’s du travail anti-op ressifA. travers ce pr i sm, nous po uondskg ager certaines des re’sistances qui sz rviennent au sein &S organismes progressistes et qui agissent contre les progres anti-oppressifs.